+0

0
377
3

if (x+2) is a factor of f(x) =x^3+3x^2-kx+4

what is k? I need this explained this is an example ,,, i dont understand how to solve this type of problems ! Your help is appreciated

Guest Jun 24, 2014

#1
+91469
+10

if (x+2) is a factor of f(x) =x^3+3x^2-kx+4

then

(x+2)(something)=x^3+3x^2-kx+4

consider if x=-2  then

(-2+2)(something)=x^3+3x^2-kx+4

But -2+2=0 and if you multiply anything by zero then the answer is zero, that is;

(-2+2)(something)=x^3+3x^2-kx+4=0

So what this is saying is that  (x+2) is a factor IF x=-2 is a root, that is, f(-2) =0

so

\$\$f(x)=x^3+3x^2-kx+4\\\\
f(-2)=(-2)^3+3(-2)^2-k(-2)+4\\\\
f(-2)=-8+12+2k+4\\\\
f(-2)=8+2k\\\\\$\$

Now if (x+2) is a factor then f(-2)=0 so

\$\$8+2k=0\\

2k=\:-8\\

k=\:-4\\\$\$

BY THE WAY this is called remainder theorum

If (x+a) is a factor of f(x) then f(-a)=0

I've just explained why.  If you have a good maths brain this will help a lot.

Melody  Jun 24, 2014
Sort:

#1
+91469
+10

if (x+2) is a factor of f(x) =x^3+3x^2-kx+4

then

(x+2)(something)=x^3+3x^2-kx+4

consider if x=-2  then

(-2+2)(something)=x^3+3x^2-kx+4

But -2+2=0 and if you multiply anything by zero then the answer is zero, that is;

(-2+2)(something)=x^3+3x^2-kx+4=0

So what this is saying is that  (x+2) is a factor IF x=-2 is a root, that is, f(-2) =0

so

\$\$f(x)=x^3+3x^2-kx+4\\\\
f(-2)=(-2)^3+3(-2)^2-k(-2)+4\\\\
f(-2)=-8+12+2k+4\\\\
f(-2)=8+2k\\\\\$\$

Now if (x+2) is a factor then f(-2)=0 so

\$\$8+2k=0\\

2k=\:-8\\

k=\:-4\\\$\$

BY THE WAY this is called remainder theorum

If (x+a) is a factor of f(x) then f(-a)=0

I've just explained why.  If you have a good maths brain this will help a lot.

Melody  Jun 24, 2014
#2
0

Guest Jun 24, 2014
#3
+91469
0

You are welcome.

Melody  Jun 24, 2014

### 4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details